Process Innovation Improves Trial Operation Efficiency. - Choi, Yun Jung; Kim, Kyu-pyo; Park, Sumi; Park, MiYeon; Kim, Sulhwa; Kim, Younkyoung; Bae, Kyun-Seop; Beck, Sung-Ho; Choi, Ki-Eun; Chung, Jong Woo; Lim, Young–Suk; Kim, Tae Won (Therapeutic Innovation & Regulatory Science, 2016)
Background: Despite the fact that unaddressed delays in clinical trial operation could severely compromise the overall effort invested, there seems to be a lack of concerted effort in reforming such delays. This study evaluated the composite effect of initiatives in reforming trial operation efficiency. Methods: A high-volume academic medical center in Korea has implemented various initiatives to improve the trial operation efficiency by expediting times from institutional review board (IRB) submission to approval, from IRB submission to trial open for subject enrollment, and from trial open to first patient-in. The initiatives include implementation of the protocol preliminary review, parallel processing of the clinical trial agreement review in line with the protocol submission to the IRB, and involvement of project manager for operational risk management. Times from IRB submission to approval, from IRB submission to trial open, and from trial open to first patient-in before and after implementation of initiatives were compared. Results: The median time required in IRB approval was meaningfully shorter in the postinitiative group (19 vs 14 days; P < .001). The median times from IRB submission to trial open for subject enrollment and from trial open to first patient-in were reduced significantly in the postinitiative group (trial open: 25 vs 18 days, P < .001; first patient-in: 111.5 vs 100 days, P = .014). Conclusions: The initiatives were effective in reforming trial operational efficiency. Additional studies to address the cause of operational delay and modifiable factors influencing subject enrollment are needed to further improve operational efficiency.